Differences in Grip Strength, Adductor Strength and External Hip Rotation Range of Motion Between Trained Grapplers and Recreationally Trained Males - Keating, T; Kennedy, E; Rivera, A (Journal of strength and conditioning research, 2011)
Combative sports such as mixed martial arts and submission grappling have grown in popularity in recent years. There is a relative paucity of research on the functional characteristics of grapplers (GR). Such data may inform trainers and coaches about the training needs of this population and may assist in identifying those with the potential for success. PURPOSE: The purpose of this investigation was to compare grip strength (GS), adductor strength (AS) and hip external rotation range of motion (ER) between grapplers and recreationally trained males. These variables were selected based on interviews with coaches and practitioners concerning important characteristics for success as well as for ease of application. METHODS: Ten GR and ten recreationally trained males (RT) volunteered for participation. GR included athletes currently training in the arts of Brazilian Jiu-Jitsu and Russian SAMBO in the New York City area. RT were agematched and recruited from fitness facilities in the same geographical area and were not involved in any sport-specific training regimen. All subjects were assessed in the evening in the "cold" condition for consistency of measurement. A digital GS dynamometer and a universal palm-held dynamometer, placed between the legs, were used to attain strength measures. A standard goniometer assessed ER while supine and knees/hips at 90 degrees. RESULTS: Independent t tests yielded the following: GR scored higher for all variables (GS 54.7 ± 6.2 vs. 50.7 ± 4.2 kg, AS 57.9 ± 10.8 vs. 40.1 ± 16.1 kg, ER 51.8 ± 11.4 vs. 39.1 ± 10.5 degrees. After applying the Bonferroni adjustment (p<.016), significance was revealed only for AS with strong trends in the other variables. Conclusion: There appear to be physiological differences, due apparently to training, between GR and RT. Practical Application: In designing training programs for competitive GR, added attention to GS, AS and ER may be warranted. [PUBLICATION ABSTRACT]